국내 선물시장에서의 증거금률 산정모형에 관한 연구 - 김학겸(Hak-kyum Kim); 박진우(Jin-woo Park); 안희준(Hee-joon Ahn) (한국증권학회지, 2017)
본 연구에서는 한국거래소에 상장된 선물상품을 대상으로 현행 KRX 모형, 역사적 시뮬레이션(HS), 지수가중 이동평균법(EWMA), GARCH 모형을 통해 산출한 증거금률을 비교하고, 사후검증(Back Test)을 통해 각 모형에서 산출된 증거금률의 정확성과 효율성을 검증하고 있다. 분석결과 증거금률은KRX 모형과 HS 모형이 EWMA 모형과 GARCH 모형에 비해 높게 나타났다. 초과횟수와 초과비율은증거금률이 높게 산출된 KRX 모형에서 가장 작은 결과를 보여주었다. 커버리지 테스트에서는EWMA 모형이 정확성 측면에서 가장 우수한 것으로 분석되었다. 모형의 효율성 측면에서는 전반적으로 EWMA 모형이 다른 모형에 비해 효율적인 것으로 나타났다. 현재 한국거래소의 증거금률은다소 지나치게 보수적으로 운용되는 경향이 있으므로 향후 EWMA 모형 등으로 증거금률 산정모형을변경하는 방안을 제안한다. 또한, 증거금률 변경주기를 단축할 경우 증거금률은 낮추면서도 결제불이행 위험은 증가시키지 않을 수 있으므로 증거금률 변경주기를 단축하는 것이 바람직하다고판단된다. 아울러 위험노출기간이 길어질 경우 모형에서 제시한 유의수준보다 높은 초과비율을보이고 있으므로 연휴 등으로 위험노출기간이 길어지는 경우에는 이에 상응하는 조치가 필요할 것으로보인다. This study examines four margin models in order to identify which one offers the most effective margin estimates for the futures contract traded on the Korea Exchange (KRX). The models considered in the study include the KRX model which is currently adopted by the exchange, the historical simulation (HS) model, the exponentially weighted moving average (EWMA) model, and the generally autoregressive conditional heteroscadasticity (GARCH) model. We backtest the four models in order to examine the accuracy and efficiency of their estimates. We find that the required margins estimated by the KRX and HS models are larger than those estimated by the EWMA and GARCH models, and that among the four models the KRX model produces the lowest violation and failure rates, indicating that the current margin requirements set by the KRX are excessively conservative. Our analysis further indicates that the EWMA and GARCH models are superior to the others in terms of the accuracy and efficiency with the EWMA model having a edge over the GARCH model. Overall, these results suggest that the KRX may consider changing its margin model to either the EWMA or GARCH model. KCI Citation Count: 0